At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
[tex] f(x)=x^2+3 \\ g(x)= -x-1 \\ 1. (g+f)(2)=g(2)+f(2)=(-x-1)+ (x^{2} +3)= x^{2} -x+2= (2)^{2} -(2)+2=4 \\ 2. (f/g)(1)=\frac{f(1)}{g(1)}= \frac{x^2+3}{-x-1} = \frac{(1)^2+3}{-(1)-1} = \frac{4}{-2} =-2[/tex]
[tex]3. (g-f)(6) =g(6)-f(6)=(-x-1)-( x^{2} +3)=- x^{2} -x-4 \\ =- (6)^{2} -(6)-4=-46[/tex]
[tex]3. (g-f)(6) =g(6)-f(6)=(-x-1)-( x^{2} +3)=- x^{2} -x-4 \\ =- (6)^{2} -(6)-4=-46[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.